2009
DOI: 10.3748/wjg.15.1065
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine impedes human pancreatic tumor growth and metastasis development in nude mice

Abstract: AIM:To study the action of aminoguanidine on pancreatic cancer xenografts in relation to cell proliferation, apoptosis, redox status and vascularization. METHODS:Xenografts of PANC-1 cells were developed in nude mice. The animals were separated into two groups: control and aminoguanidine treated. Tumor growth, survival and appearance of metastases were determined in vivo in both groups. Tumors were excised and ex vivo histochemical studies were performed. Cell growth was assessed by Ki-67 expression. Apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Anecdotally, the one cell line not affected by L-NAME, PANC-1, was the only line with undetectable levels of activated eNOS (13). In agreement, N -nitro- l -arginine (L-NNA), an insoluble active metabolite of L-NAME, halved both subcutaneous and orthotopic xenograft tumor growth of the human PDAC cell line L3.6pl (41) and aminoguanidine, a broad NOS inhibitor with some specificity for iNOS, decreased tumor growth when given at high doses (42). …”
Section: Resultsmentioning
confidence: 94%
“…Anecdotally, the one cell line not affected by L-NAME, PANC-1, was the only line with undetectable levels of activated eNOS (13). In agreement, N -nitro- l -arginine (L-NNA), an insoluble active metabolite of L-NAME, halved both subcutaneous and orthotopic xenograft tumor growth of the human PDAC cell line L3.6pl (41) and aminoguanidine, a broad NOS inhibitor with some specificity for iNOS, decreased tumor growth when given at high doses (42). …”
Section: Resultsmentioning
confidence: 94%
“…It has been demonstrated that cancer-relevant mediators could include IL-1β [210], TNF-α [211], NF-κB [209] and STAT-1 [212], among others. In fact, NO blockage has reached promising results in experimental models, inhibiting tumor growth [213], prolonging survival [214], and reducing metastasis [215]. These data indicate that the pharmacological impairment of iNOS functioning may be useful in patients diagnosed with metastatic disease, since sustained high levels of systemic NO are reported in such patients [216–219].…”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…To estimate the role of iNOS protein in berberineinduced apoptosis, the cells were treated with iNOS selective inhibitor, aminoguanidine (AG). Figure 3b showed that AG did not have a remarkable effect on T47D cell viability, whereas it has an inhibitory effect on some tumor cell growth [33]. Despite the no significant effect on cell vialbility, AG had a remarkable inhibitory effect on NO production (Fig.…”
Section: Discussionmentioning
confidence: 89%